2005
DOI: 10.1089/neu.2005.22.822
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Levels of Pro- and Anti-Inflammatory Mediators in Cerebrospinal Fluid and Plasma: A Normative Study

Abstract: Numerous recent studies have reported a significant inflammatory reaction in the brain and the systemic circulation following traumatic brain injury (TBI), infection, or neoplasm of the brain with a sequential release of pro- and anti-inflammatory mediators. Although there is growing knowledge and understanding of the mechanisms leading to the often poor outcome of these patients, only a limited database exists on the physiological expression of pro- and anti-inflammatory cytokines and molecules in plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…The values of CSF IL-8 among healthy volunteers also support physiological synthesis of IL-8 by the CNS (Maier et al 2005). Under pathological conditions such as meningitis or astrocytoma development synthesis of IL-8 in the brain is pronounced resulting in the raise of the cytokine values in CSF (Mastroianni et al 1998;Choi 2002).…”
Section: Discussionmentioning
confidence: 52%
“…The values of CSF IL-8 among healthy volunteers also support physiological synthesis of IL-8 by the CNS (Maier et al 2005). Under pathological conditions such as meningitis or astrocytoma development synthesis of IL-8 in the brain is pronounced resulting in the raise of the cytokine values in CSF (Mastroianni et al 1998;Choi 2002).…”
Section: Discussionmentioning
confidence: 52%
“…The intra assay coefficient of varia tion was below 20% for all analytes presented. In analogy with the study by Maier and colleagues, 31 particularly reliable detec tions of IL 6 and IL 8 was achieved. The limits of detection in our analysis were as follows: IL 1β (0.06 pg/mL), IL 2 (0.23 pg/mL), IL 4 (0.20 pg/mL), IL 6 (0.26 pg/mL), IL 8 (0.12 pg/mL), IL 10 (0.23 pg/mL), IL 18 (1.57 pg/mL), TNF α, (0.18 pg/mL), IFN α 2a (0.74 pg/mL) and IFN γ (0.24 pg/mL).…”
Section: Cytokine Analysesmentioning
confidence: 63%
“…[14][15][16] Although this discrepancy may relate to fluctuations of cytokines along with various states of the disease, the cytokine profile of the brain may also clearly differ from that of the periphery. 8,17,18 Supporting a central origin of the presently observed increased IL-1β concentration, a recent postmortem study demonstrated higher protein and mRNA levels of IL-1β in patients with bipolar disorder. 13 However, since peripheral cyto kines may access the brain through a damaged blood-brain barrier or through volume diffusion where the barrier is absent, such as in paraventricular organs, a tentative contribution of peripheral cytokines to the brain in bipolar disorder should not be disregarded.…”
Section: Discussionmentioning
confidence: 90%
“…The bidirectional communication between the immune system of the brain and that of peripheral organs is complex, 7 and serum cytokines do not predict brain cytokine activation in healthy volunteers. 8 Hence, the immune system of the brain, including local cytokine release from microglia and astrocytes, may be independent of the immune system in peripheral organs. The aim of the present study was to investigate an immune activation in the brains of patients with bipolar disorder by analyzing well-characterized cytokines in the cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%